P-0045: Treatment with spherical particle carbon for Anal Fistula in Crohns Disease - Fukuda, Y; Takazoe, M; Fukushima, T (Inflammatory bowel diseases, 2007)
and PurposeCrohn's disease (CD) often accompanies with small intestinal lesion in addition to large intestinal lesion. Nutritional therapy, a standard therapy for pediatric CD in US and Europe, has been applied on adult CD in Japan. According to the Japanese therapeutic guideline for CD from Japanese Ministry of Health, Labour and Welfare, the first choice is nutritional therapy with dietary management, the second is drug treatment and the third is surgical treatment.When nutritional therapy is accompanied with drug treatment, superior remission rate for luminal CD is obtained. However we sometimes see little improvement for the closure of anal fistula because of lasting diarrhea, or the cases where nutritional therapy is not well performed. From these points of view, we examined the effect of AST-120 in the cases where nutritional therapy was performed either adequately or inadequately.MethodsThe subjects were 37 CD patients who had some improvement in disease status by nutritional management and still had diarrhea and active anal fistula, and 41 CD patients who had not received nutritional management and had active anal fistula. To these patients, AST-120 was administered to see the healing effects on anal fistula. Administration period was 8-weeks and the closure of anal fistula was compared between two groups. To evaluate the disease status, CDAI and PDAI were used. CRP and erythrocyte sedimentation were used for inflammation assessment. Blood tests for liver function, anemia and so on, were performed. Rectal and pelvic examination was performed as much as possible by CT scan and MRI.ResultsIn nutritional therapy group, 21 patients experienced the closure of anal fistula, while it was seen in 13 patients in non-nutritional therapy group. There was a slight abdominal pain with the patient having stricture in small and large intestines, however there was no serious side effect. Approximately fifty percent of the patients, whose anal fistulas were confirmed to be closed, had recurrence within 6 to 12 months.ConclusionsThe clinical utility of AST-120 was proved to be high in terms of anal fistula closure in Crohn's disease. AST-120 treatment was more useful in the cases that nutritional management was simultaneously performed with AST-120 treatment and effective to obtain the improvement of intestinal lesions, in comparison with the cases that there were no nutritional therapy performed and no clear improvement of intestinal lesions. AST-120 treatment should be applied in the cases where drug treatment and/or biological therapy can control the luminal lesions, but patients still suffer from active anal fistula.